Faculty Research Productivity of Isabela State University Echague Cluster Towards Developing a Faculty Development Program - Eslava, Wilmae Nissah; Cammayo, Eva (International Journal of Sustainability and Advanced Integrated Research, 2026)
Research productivity is widely regarded as a vital aspect of Higher Education Institutions (HEIs), as it significantly contributes to academic excellence, innovation, institutional reputation, and global competitiveness. This study assessed the research productivity of faculty-researchers at the Isabela State University (ISU) Echague Cluster, with the aim of developing a faculty development program. Specifically, it examined the profile of the respondents and evaluated their research productivity in terms of research output, research funding and grants, innovation and intellectual property, research engagement and collaboration, research utilization and impact, and recognition and awards. The study also sought to determine whether significant differences existed in research productivity when respondents were grouped according to their profile. A descriptive-comparative research design was employed, involving 138 faculty researchers from the Echague, Jones, and Angadanan campuses, who were selected through purposive sampling. Data were gathered using a validated survey questionnaire and analyzed using frequency counts, percentages, means, ANOVA, and t-tests. The findings indicate that most respondents were young professionals with doctorate degrees, moderate years of service, and substantial teaching workloads. Faculty members actively participated in conference presentations and institutionally funded research projects; however, limited productivity was observed in indexed publications, patents, international collaborations, and research recognition. Significant differences in research productivity were noted according to educational attainment, training attended, designation, plantilla position, and campus assignment. The study supports SDG 4, SDG 9, and SDG 17 by promoting quality higher education, innovation, and research partnerships. Its sustainability impact lies in strengthening institutional research culture, academic productivity, knowledge generation, and long-term faculty development. The study concluded that enhanced institutional support, capability-building activities, mentorship programs, and funding opportunities would be beneficial for improving faculty research productivity and strengthening the research culture within the university.